The Effectiveness of Community Food Barns in Batam City's Food Diversification Program - Denti Permatasari; Timbul Dompak; Lubna Salsabila; Etika Khairina (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2023)
The objective of this research is to examine and identify the factors that influence the effectiveness of food barns in upholding food security, as well as the challenges faced by the residents of Batam City in establishing and reinforcing these food storage facilities to achieve food security. Moreover, it aims to assess the quality of available food and enhance its diversity, encompassing options rich in carbohydrates, protein, vitamins, and other essential minerals. Food barns are an integral part of the community's food reserve system and coexist harmoniously with rice culture. A key strategy to ensure food self-sufficiency is through the diversification of food consumption. This research employs qualitative methods and draws on limited research from books, journals, and other relevant literature sources. The findings shed light on the significant role played by food barns in ensuring food security. They serve as vital storage locations for the entire population, addressing food shortages during crop failures or periods of famine, and contributing to the collective income. However, the study also reveals various challenges in the growth and development of food barns, including issues related to food access, limited facilities, availability of food supplies, and health or nutritional concerns. These factors drive the necessity for the establishment of sustainable food barns. Consequently, the implications of the research highlight the limited presence of food barns and the need for increased storage capacity to effectively meet the demands of the community.